2002
DOI: 10.1021/la0116903
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Platinum-Based Electrocatalysts on Multiwalled Carbon Nanotubes for Proton Exchange Membrane Fuel Cells

Abstract: A higher yield of functionalized carbon nanotubes (CNTs) was obtained by treatment of CNTs in HNO3 or H2SO4-K2Cr2O7. The deposition of platinum nanoparticles and nanoclusters on these functionalized multiwalled carbon nanotubes by electroless plating was facilitated by a two-step sensitization-activation pretreatment. The deposition was sensitive to the aging time of the sensitizing solution and the pH of the plating solution. The resulting electrocatalysts were characterized by transmission electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
339
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 551 publications
(345 citation statements)
references
References 42 publications
4
339
1
1
Order By: Relevance
“…Pt/C) have been considered as the most effective elecrocatalysts for ORR in PEM fuel cells due to their high activities and good stabilities. [1][2][3][4][5][6][7][8][9] However, the issues of high cost, scarce sources and long-term durability limit their large-scale production and hinder the commercialization of PEM fuel cells. [10][11][12][13][14] In order to decrease the cost of electrocatalysts and eliminate their dependence on noble metals, various non-noble metal catalysts have been explored recently as alternatives to the Pt-based electrocatalysts, which include chalcogenide catalysts, [15][16][17][18][19] transition metal macrocyclic compounds, [20][21][22] transition metallic oxides [23][24][25][26][27] and carbon-based catalysts.…”
mentioning
confidence: 99%
“…Pt/C) have been considered as the most effective elecrocatalysts for ORR in PEM fuel cells due to their high activities and good stabilities. [1][2][3][4][5][6][7][8][9] However, the issues of high cost, scarce sources and long-term durability limit their large-scale production and hinder the commercialization of PEM fuel cells. [10][11][12][13][14] In order to decrease the cost of electrocatalysts and eliminate their dependence on noble metals, various non-noble metal catalysts have been explored recently as alternatives to the Pt-based electrocatalysts, which include chalcogenide catalysts, [15][16][17][18][19] transition metal macrocyclic compounds, [20][21][22] transition metallic oxides [23][24][25][26][27] and carbon-based catalysts.…”
mentioning
confidence: 99%
“…The synthesis methods reported in the literature for Pt/CNTs are wet chemical method [16,17], electroless plating [18], electrodeposition [19], selfassembly [20] and supercitrical fluid [21]. However, homogenous deposition of Pt nanoparticles on the inert surface of CNTs is still a challenge in current technology [22].…”
Section: Pt/mwcnts Synthesis Methodsmentioning
confidence: 99%
“…Halder et al (Halder et al, 2009) tried a surface treatment of CNTs by its mixing with a combination of concentrated HNO 3 and H 2 SO 4 which gave very good surface functionalization on the wall of CNTs. Liu et al (Liu et al, 2002) reported a high density of oxygen containing species on the CNT surface by a K 2 Cr 2 O 7 /H 2 SO 4 oxidative treatment. In general, the oxidative treatment technique can functionalize CNTs with oxygencontaining functional groups on their walls, which could increase the surface binding sites of CNTs, avoid the aggregation of the subsequent deposited metal NPs, improve the dispersion of metal NPs, and reduce the average size of metal NPs deposited.…”
Section: Covalent Functionalization 211 Oxidative Treatment Of Cnt mentioning
confidence: 99%